2020
DOI: 10.1002/ejoc.201901659
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on Ring‐Contracting Skeletal Rearrangement from Porphycene to Isocorrole by Experimental and Theoretical Methods

Abstract: In this study, the ring contracting skeletal rearrangement reaction in one‐pot under basic conditions from octaethylporphycene to two types of isocorroles, i.e., the meso‐formyl and meso‐free forms, was confirmed and the reaction mechanism was proposed by the comparative analyses of the experimental and theoretical studies. The electron accepting nature of the porphycene and imine‐amine conversion of pyrrole rings make it possible to react with hydroxide ions and the following reaction to afford isocorroles. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Although there are extensive studies of visible and NIR absorption in the literature, little has been reported on the emission properties of the isocorroles. The only reported NIR emission of a related species involves 10-silacorroles 32 and an extended isocorrole, 33 and both exhibit emission within the 700–1200 nm range. The compounds reported here all exhibit broad single-peak NIR phosphorescence between 850 and 1500 nm when excited with a 405 nm LED excitation light source ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are extensive studies of visible and NIR absorption in the literature, little has been reported on the emission properties of the isocorroles. The only reported NIR emission of a related species involves 10-silacorroles 32 and an extended isocorrole, 33 and both exhibit emission within the 700–1200 nm range. The compounds reported here all exhibit broad single-peak NIR phosphorescence between 850 and 1500 nm when excited with a 405 nm LED excitation light source ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%